GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 362 species occurrences available in GBIF matching the query: TaxonKey: Atelopus longirostris Cope, 1868. The dataset includes 362 records from 12 constituent datasets: 1 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 37 records from Museum of Comparative Zoology, Harvard University. 3 records from NRM-Herpetology. 11 records from AMNH Herpetology Collections. 3 records from ICN - Universidad Nacional de Colombia. 9 records from Natural History Museum (London) Collection Specimens. 50 records from NMNH Extant Specimen and Observation Records. 216 records from Partial Amphibians Collection. 10 records from UMMZ Herpetology Collection. 2 records from CAS Herpetology (HERP). 17 records from KUBI Herpetology Collection. 3 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences